Climate change [electronic resource]: classroom video issues 2 - Video Education Australasia (Australia, AT. : VEA, 2008)
This Australian-made, curriculum fir program poses questions for debate and discussion in the classroom about climate change. It presents expert opinions, statistics and historical references presenting two sides of the story, and ultimately ask us, how worried should we be and what can or should we do to avert climate change? This is an informed and timely look at this most critical issue. Source : VEA webpage : http://www.veavideo.com.